2022
DOI: 10.1021/acs.inorgchem.1c04022
|View full text |Cite
|
Sign up to set email alerts
|

Structural Phase Transitions in closo-Dicarbadodecaboranes C2B10H12

Abstract: The crystal structures of three thermal polymorphs (I, II, and III) for each isomer of closo -dicarbadodecaboranes C 2 B 10 H 12 ( ortho , meta, and para ) have been determined by combining synchrotron radiation X-ray powder diffraction and density functional theory calculations. The structures are in agreement with previous calorimetric and spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…In C 2 B 10 H 12 , the transition between the ordered and disordered phases involves an intermediate, partially disordered phase ( Pa 3̄), which shows uniaxial rotation of the anion. 39 A similar transition with two high-temperature phases has been proposed for Li 2 B 10 H 10 in ref. 33, 37 and two phases have indeed been observed.…”
Section: Resultssupporting
confidence: 69%
“…In C 2 B 10 H 12 , the transition between the ordered and disordered phases involves an intermediate, partially disordered phase ( Pa 3̄), which shows uniaxial rotation of the anion. 39 A similar transition with two high-temperature phases has been proposed for Li 2 B 10 H 10 in ref. 33, 37 and two phases have indeed been observed.…”
Section: Resultssupporting
confidence: 69%
“…Furthermore, the previous paragraph concluded that the larger cell size was in favor of high cationic diffusion and higher anionic reorientational motion, which could also reduce the T tran because of the larger interstitial space easing the anionic rotation. Thus, a guideline would be keeping smaller size cations in a larger cell, which could be achieved by partial adding of C 2 B 10 H 12 [72,73], where the effective anionic radius is expected to be larger because of higher charge in C, offering a larger cell volume compared to LiCB…”
Section: Atomistic Mechanisms and Cationic Pathmentioning
confidence: 99%
“…Thus, a guideline for superior materials could be keeping a smaller-sized cation in a bigger simulation cell, as observed in Na x (CB 11 H 12 ) x (meta-C 2 B 10 H 12 ) 1 x [73]. However, in real materials both the cation sizes and the anionic arrangement play combined roles.…”
Section: Schimatic 2dmentioning
confidence: 99%
“…C 2 B 10 H 12 , which both are very (electro-)chemically and thermally stable. 51–56 The monovalent charge of the [CB x H x +1 ] − anion as compared to the divalent [B x H x ] 2− also results in only half the amount of cations required for charge neutrality, effectively resulting in more available cation positions. Several solid solutions have been reported, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…C 2 B 10 H 12 , which both are very (electro-) chemically and thermally stable. [51][52][53][54][55][56] H 14 ] x , but the nido-boranes usually have lower stability compared to the closo-boranes. 61,62 Well-defined solid solutions solved from single crystal X-ray diffraction data has also been reported for Pd[Br 1.133 Cl 0.867 (1,2-…”
Section: Introductionmentioning
confidence: 99%